A cross-sectional mixed methods protocol to describe correlates and explanations for a long duration of untreated psychosis among patients with first episode psychosis in Uganda. Issue 7 (16th July 2019) - Mwesiga, Emmanuel Kiiza; Nakasujja, Noeline; Ongeri, Linnet; Semeere, Aggrey; Loewy, Rachel; Meffert, Susan
Abstract : Introduction: Among patients with psychotic disorders, the 'duration of untreated psychosis' (DUP) is a predictor of key outcomes such as symptom remission and quality of life. In sub-Saharan Africa, DUP is up to five times longer than in high-income countries, with many patients going without antipsychotic medication for 5 years or longer. One contributor to this high DUP may relate to cultural norms that drive use of alternative and complementary therapies (ACTs) as first-line treatment strategies, rather than biomedical care with antipsychotic medicine. We aim to 1 determine the prevalence and factors associated with DUP and ACT use in Uganda, and 2 Identify factors that drive patient and family choices to use ACT as a first-line treatment strategy. Methods and analysis: We will leverage on an ongoing cohort study at the national psychiatric and teaching hospital in Uganda. The parent study is an observational cohort design following antipsychotic naïve adults with a first episode of psychosis without substance use, HIV/AIDS or syphilis. The embedded study will use a mixed methods design including quantitative assessment of parent study participants with the Nottingham Onset Schedule-DUP to determine the DUP. Qualitative assessment will focus on patient and caregiver perceptions and use of ACT and its impact on DUP among patients with psychosis using in-depth interviews. Ethics and dissemination: The study has received ethical approval from the school of medicine research and ethics committee of the college of health sciences at Makerere University. It has also received institutional support to perform the study from the Infectious Diseases Institute and Butabika hospital. Besides publication of the work in reputable peer-reviewed journals, we hope that this work will lead to evidence-based discussions on the need for early interventions to reduce DUP in Uganda.